2017
DOI: 10.3390/molecules22030430
|View full text |Cite
|
Sign up to set email alerts
|

The Emission of the Floral Scent of Four Osmanthus fragrans Cultivars in Response to Different Temperatures

Abstract: Floral scent is an important part of volatile organic compounds (VOCs) emitted from plants, and is influenced by many environmental and endogenous factors. To investigate the influence of temperature on the emission of the floral scent of Osmanthus fragrans, the number of chemical compounds and their relative release amounts from four cultivars of O. fragrans under different temperature treatments, were identified using the solid-phase microextraction (SPME) technique and gas chromatography-mass spectrometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…O. fragrans is of high economic value in China . The highly distinct floral fragrance of O. fragrans has been the subject of extensive research . A variety of volatile organic compounds (VOCs) have been identified in O. fragrans flowers, including alcohols, aromatic compounds, ketones, terpenoids, and esters .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…O. fragrans is of high economic value in China . The highly distinct floral fragrance of O. fragrans has been the subject of extensive research . A variety of volatile organic compounds (VOCs) have been identified in O. fragrans flowers, including alcohols, aromatic compounds, ketones, terpenoids, and esters .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The highly distinct floral fragrance of O. fragrans has been the subject of extensive research. [4][5][6][7][8] A variety of volatile organic compounds (VOCs) have been identified in O. fragrans flowers, including alcohols, aromatic compounds, ketones, terpenoids, and esters. 4 Some investigations have shown the contributions of certain VOCs to the specific fragrances of particular cultivars.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The profound diversity in the total carotenoid concentrations of the two clusters was determined by the transcript levels of OfCCD4 [22]. The main volatile organic compounds in petals of O. fragrans are linalool, α-ionone, β-ionone, and γ-decalactone, and 19 • C would promote the emission of a floral scent [23]. Studies have shown that the biosynthesis of volatile compounds in O. fragrans is caused by the OfCCD4 instead of OfCCD1 [24,25].…”
Section: Introductionmentioning
confidence: 99%